Reanimating ELIZA, the world’s first chatbot Inventing ELIZA Sarah Ciston, David M. Berry, Anthony C. Hay, Mark C. Marino, Peter Millican, Jeff Shrager, Arthur I. Schwarz, Peggy Weil The MIT Press, 2026. 350 pp. - Simson L. Garfinkel (Science, 2026)
A simple program created in the 1960s laid the groundwork for future conversational computers